Integrating Human Resources Management and Digital Competencies: A Strategic Approach in Higher Education - Teti Rohayati (STAI Hubbulwathan Duri, 2024)
This paper explores the integration of Human Resources Management (HRM) and digital competencies as a strategic approach in higher education institutions. In this context,